PENGARUH PENGENDALIAN TERHADAP EFEKTIVITAS PENERTIBAN IZIN USAHA PEMANFAATAN AIR BAWAH TANAH PROVINSI JAWA BARAT - Arianto, Febri; Rachmawati, Emi (Jurnal Sosial Politik Unla, 2023)
The problem with this research is the inefficiency of the approval of underground water exploitation undertakings in the West Java Province. Based on the problem, the researchers formulate the problem as follows: How great is the impact of the control on the effectiveness of the issuance of underground water exploitation permits in the West Java province? In analyzing the problems studied, the author proposes the theory of control of Handoko (2003:359) while the theories of effectiveness of Duncan in Zulkarnain (2012:32). The hypothesis was formulated as follows: "The great impact of control on the effectiveness of licensing underground water exploitation undertakings in the West Java province. The research method used is this descriptive analysis with a quantitative approach. Data sources obtained from primary and secondary data sources. Data-gathering techniques are used by means of observation, interviews, and diffusion. The population consists of Apparatur Branch Service Energy and Mineral Resources Region V Fields of Land Water and Land Water Entrepreneurs in Bandung Prefecture. The test results of the proposed hypothesis show that the control variable has a moderate and significant relationship between the control over the effectiveness of the issuance of underground water exploitation permits in the West Java Province. In addition, other variables that influence the effectiveness are coordination, monitoring and evaluation variables. Thus, the results of this study are empirically tested.